Entrepreneurship in the Global Firm. - Verbeke, Alain (Progress in International Business Research, 6., 2011)
This 15-chapter volume provides the latest research insights from the international business field on entrepreneurship in the global firm. It provides a unique, comprehensive perspective on the wide variety of conceptual and managerial issues that arise as a result of entrepreneurial action in firms operating in the global economy.